UPAYA MENINGKATKAN KEPUTUSAN PEMBELIAN PADA KEMBANG JAWA MOTOR DITINJAU DARI HARGA, PROMOSI DAN PELAYANAN - Anggraeni, Septi (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2022)
The distribution of Honda motorcycles in Trenggalek is only controlled by the Kembang Jawa Motor Dealer and Karya Agung Motor, which are rival dealers. During the pandemic, the Kembang Jawa Motor Dealer applies a strategy to maintain sales and even the existing marketing strategy is expected to increase sales. This study was conducted to analyze efforts to increase sales as seen from consumer buying interest by using price indicators, promotions, and services at Kembang Jawa Motor Trenggalek dealers partially and simultaneously. This research is a quantitative type, which uses a population in the form of consumers at the Kembang Jawa Motor Trenggalek dealer. The sample used by researchers amounted to 40 respondents with details 10 times the number of existing variables. The sampling used accidental sampling technique. The results of this study indicate that prices, promotions, and services have a partial and simultaneous influence on purchasing decisions